Orientation dependent interlayer stacking structure in bilayer MoS2 domains. Issue 35 (24th August 2017) - Wang, Shanshan; Sawada, Hidetaka; Allen, Christopher S.; Kirkland, Angus I.; Warner, Jamie H.
Abstract : We have studied the atomic structure of small secondary domains that nucleate on monolayer MoS2 grown by chemical vapour deposition (CVD), which form the basis of bilayer MoS2 . Abstract : We have studied the atomic structure of small secondary domains that nucleate on monolayer MoS2 grown by chemical vapour deposition (CVD), which form the basis of bilayer MoS2 . The small secondary bilayer domains have a faceted geometry with three-fold symmetry and adopt two distinct orientations with 60° rotation relative to an underlying monolayer MoS2 single crystal sheet. The two distinct orientations are associated with the 2H and 3R stacking configuration for bilayer MoS2 . Atomic resolution images have been recorded using annular dark field scanning transmission electron microscopy (ADF-STEM) that show the edge termination, lattice orientation and stacking sequence of the bilayer domains relative to the underlying monolayer MoS2 . These results provide important insights that bilayer MoS2 growth from 60° rotated small nuclei on the surface of monolayer MoS2 could lead to defective boundaries when merged to form larger continuous bilayer regions and that pure AA′ or AB bilayer stacking may be challenging unless from a single seed.